Socio-economic condition of fishermen and intermediaries involved in marine fish marketing chain in Coxs Bazar area, Bangladesh - Ahsan, Md Khabirul; Runa, Nusrat Sultana; Ghosh, Subrata Kumar; Hasan, Muhammad Mehedi; Kamal, Md (Asian Journal of Medical and Biological Research, 2016)
Study was conducted to know the socio-economic condition of the fishermen and intermediaries of fish marketing chain in Coxs Bazar area, Bangladesh. Socio-economic condition of the fishermen and intermediaries were not so good in the study area. It was found that about 35% fishermen and intermediaries were illiterate, 16% fishermen and intermediaries were semiliterate who only could write their names. 55% household of the fishermen and intermediaries had tin shed house with tin wall. Average income for most of fishermen and intermediaries was about Tk. 400-500 and 66% were found to borrow money from different source for continuing their business. Poor road and transport facilities, lack of credit facilities, insufficient supply of ice, inadequate training facilities and large number of intermediaries in the chain were the main problems of the marine fish marketing chain. It is therefore necessary to provide institutional and organizational support, government support, extension service and training facilities to the market operators for sustainable fish marketing systems. Asian J. Med. Biol. Res. March 2016, 2(1): 67-73